2001
DOI: 10.1038/sj.jhh.1001205
|View full text |Cite
|
Sign up to set email alerts
|

A forced titration study of antihypertensive efficacy of candesartan cilexetil in comparison to losartan: CLAIM Study II

Abstract: An 8-week, multicentre (72 sites in the US), doubleblind, randomised, parallel group, forced titration study compared the antihypertensive efficacy of candesartan cilexetil and losartan. A total of 611 patients with essential hypertension (diastolic blood pressure 95 to 114 mm Hg) were randomised initially to candesartan cilexetil 16 mg once daily or losartan 50 mg once daily. After 2 weeks of randomised treatment, the doses of candesartan cilexetil and losartan were doubled to 32 mg and 100 mg once daily and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 10 publications
1
31
0
4
Order By: Relevance
“…13,24 Age, gender and race did not play a substantial role in the differential effects between telmisartan-HCTZ 80/25 and valsartan-HCTZ 160/25. The antihypertensive efficacy differences between telmisartan-HCTZ and valsartan-HCTZ, although small, bear clinical significance.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…13,24 Age, gender and race did not play a substantial role in the differential effects between telmisartan-HCTZ 80/25 and valsartan-HCTZ 160/25. The antihypertensive efficacy differences between telmisartan-HCTZ and valsartan-HCTZ, although small, bear clinical significance.…”
Section: Discussionmentioning
confidence: 92%
“…All combinations with the angiotensin receptor blockers were developed initially with HCTZ at a dose of 12.5 mg; these combinations typically show additive effects on blood pressure lowering regardless of which angiotensin receptor blocker was evaluated. 6,[19][20][21][22][23][24] Incremental BP-lowering effects have been observed with larger doses of hydrochlorothiazide, that is, 25 mg, in combination with the angiotensin receptor blockers, 6,19 which led to the development of the fixed-dose combination formulations used in our trial. In an earlier study by Benz and coworkers, 19 valsartan-HCTZ at a dose of 160/25 mg lowered the BP by 22/15 mm Hg compared with 18/ 14 mm Hg for valsartan-HCTZ at a dose of 160/ 12.5 mg. Trenkwalder et al 25 also showed that patients not controlled on valsartan-HCTZ 160/ 12.5 mg had an additional 8.4/8.3 mm Hg reduction in BP when the diuretic dose was increased to 25 mg.…”
Section: Principal Findingsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25] A total of 4066 patients were included in the analysis, and the design and patient characteristics of randomized clinical trials included in the meta-analysis are shown in Table 1. The majority of the trials had a randomized, doubleblind, parallel group design.…”
Section: Resultsmentioning
confidence: 99%
“…At baseline, mean clinic SBP was similar in all 3 treatment groups (Table I). At week 24, statistically significantly greater decreases in the change from baseline to week 24 in mean clinic SBP were observed for each of the AZL-M treatment groups (40 mg and 80 mg) compared with VAL 320 mg (P=.015 and P<.001, respectively), and the mean decrease was numerically greater with AZL-M 80 mg () 16.92 mm Hg) than with AZL-M 40 mg ()14.86 mm Hg). …”
Section: Changes In 24-hour Mean Sbp and Clinic Sbpmentioning
confidence: 98%